SFRP1 upregulation causes hippocampal synaptic dysfunction and memory impairment - Guadalupe Pereyra; María Inés Mateo; Pablo Miaja; María Jesús Martin-Bermejo; Marcos Martinez-Baños; Remco Klaassen; Agnès Gruart; Javier Rueda-Carrasco; Alba Fernández-Rodrigo; Esperanza López-Merino; Pilar Esteve; José A. Esteban; et al. (Cell Reports)
Summary: Impaired neuronal and synaptic function are hallmarks of early Alzheimer’s disease (AD), preceding other neuropathological traits and cognitive decline. We previously showed that SFRP1, a glial-derived protein elevated in AD brains from preclinical stages, contributes to disease progression, implicating glial factors in early pathogenesis. Here, we generate and analyze transgenic mice overexpressing astrocytic SFRP1. SFRP1 accumulation causes early dendritic and synaptic defects in adult mice, followed by impaired synaptic long-term potentiation and cognitive decline, evident only when the animals age, thereby mimicking AD’s structural-functional temporal distinction. This phenotype correlates with proteomic changes, including increased structural synaptic proteins like neurexin, which localizes in close proximity with SFRP1 in cultured hippocampal neurons. We conclude that excessive SFRP1 hinders synaptic protein turnover, reducing synaptic plasticity—a mechanism that may underlie the synaptopathy observed in the brains of prodromal AD patients.